Impact of spatial variability of shear wave velocity on the lagged coherency of synthetic surface ground motions. Issue 145 (June 2021) - El Haber, E.; Cornou, C.; Jongmans, D.; Lopez-Caballero, F.; Youssef Abdelmassih, D.; Al-Bittar, T.
Abstract: The spatial incoherence of ground motion during an earthquake can have a significant effect on the dynamic response of engineering structures such as bridges, dams, nuclear power plants and lifeline facilities. The main objective of this paper is to study the effect of anisotropic heterogeneities in a soil layer overlying homogeneous bedrock on the lagged coherency of surface ground motion. A set of numerical experiments is performed based on 2D spatial variability of shear-wave velocities modeled as a homogeneous stationary random field and discretized by the EOLE method (Expansion Optimal Linear Estimation). Seismic ground motions were simulated using FLAC 2D software in the 1–25 Hz band for a plane wave excitation with SV polarization. The soil is characterized by horizontal and vertical autocorrelation distances ranging between 5 and 20 m and 1 and 2 m, respectively, and a coefficient of variation of the shear-wave velocity varying between 5% and 40%. The synthetic seismograms calculated for 9 parameter sets (100 realizations each) clearly show seismic waves scattering and surface waves diffracted locally by the ground heterogeneities, generating large spatial variations in coherence mainly controlled by the coefficient of variation of shear-wave velocity. Consistently with existing models and experimental data, the numerical coherency curves decrease with frequency and receiver distance, however at a rate which is lower than that observed in the experimental data. This difference is probably due to intrinsic attenuation that is not accounted for in the simulations and/or to our 2D simulations that do not reproduce the complete wavefield. The numerical average coherency curves for each parameter set exhibit maxima within narrow frequency bands caused by the vertically trapped body waves and surface wave propagation properties within the average ground model. This interpretation is supported by experimental data recorded in the Koutavos-Argostoli valley (Greece). Highlights: The shear-wave velocity coefficient of variation is controlling the coherency of the surface ground motion. The effect of the horizontal autocorrelation distance is observed for small inter-receivers' distances. Maximum coherency is observed at the resonant frequencies and the Airy phase. This interpretation is validated in both numerical and experimental observations. The atanh transformation is not relevant for coherency standard variation estimation. Existing coherency models underestimate the coherency of synthetic ground motions.